Efficacy of angiotensin receptor neprilysin inhibitor in hypertension management: A systematic review and meta-analysis of clinical trials - Ramadhan, Roy N.; Rampengan, Derren DCH.; Puling, Imke MDR.; Willyanto, Sebastian E.; Tjandra, Kevin C.; Thaha, Mochammad; Multazam, Chaq ECZ.; Suryantoro, Satriyo (Narra Sains Indonesia, 2024)
Dysregulation of renin-angiotensin-aldosterone system (RAAS) often leads to hypertension and severe cardiorenal complications. Although RAAS-targeted therapies have proven effective, it remains yet optimal in reducing cardiovascular events. The aim of this study was to evaluate the efficacy and safety of angiotensin receptor neprilysin inhibitor (ARNI) compared to control in patients with hypertension. The primary outcomes were systolic and diastolic blood pressure (BP) control, along with the incidence of adverse events. A systematic review and meta-analysis was conducted according following PRISMA guidelines. A comprehensive literature search was performed across five databases: PubMed, ScienceDirect, EBSCO, Cochrane, and ProQuest, with studies identified up until 3 October 2024. The study included nine clinical trials that met the predefined eligibility criteria: (1) randomized clinical trials; (2) adult patients diagnosed with hypertension; and (3) comparison of ARNI versus control, reporting either BP control or adverse events. Quality appraisal using RoB 2.0 revealed that eight studies had a low risk of bias, and one had a high risk of bias. The pooled analysis demonstrated that ARNI is significantly more efficacious in achieving targeted systolic BP as compared to the control group (OR: 1.80; 95%CI: 1.41-2.30; p<0.001; I²=0%), and there was no statistical difference for the efficacy on diastolic BP compared to control (OR: 0.92; 95%CI: 0.75–1.13; p=0.45; I²=75%). The incidence of adverse events was not associated with ARNI (OR: 1.07; 95%CI: 0.90–1.27; p=0.46; I²=72%). In conclusion, ARNI demonstrated a favorable outcome only in systolic BP, but in diastolic BP which could be associated with inadequate duration of observation. Further studies are warranted to assess BP-lowering effect and safety profile of ARNI in a longer observation time.